Eight weeks of self-resisted neck strength training improves neck strength in age-grade rugby union players: A pilot randomized controlled trial - Attwood, M. J.; Hudd, L.-J. W.; Roberts, S. P.; Irwin, G.; Stokes, K. A. (Sports Health: A Multidisciplinary Approach, 2021)
Background: Greater neck strength is associated with fewer head and neck injuries. Neck-strengthening programs are commonly burdensome, requiring specialist equipment or significant time commitment, which are barriers to implementation.